Metaphor Performance in Children With Hearing Impairment - Wolgemuth, Keith S; Kamhi, Alan G; Lee, Rene F (Language, speech & hearing services in schools, 1998)
Metaphor comprehension and use were evaluated in children with hearing impairment (HI) who performed within normal age limits on norm-referenced measures of language. Participants were 13 children with mild-to-moderate sensorineural hearing loss and 12 children with normal hearing and normal development (10:0 to 15:7 years:months). Three verbal metaphor tasks (comprehension, preference, and completion) and one visual metaphor task, the Metaphor Triads Task (MTT), were administered. No significant group differences were found on any of the tasks. Both groups exhibited the same metaphor competence and response patterns on the four tasks. These findings add to a growing body of literature showing that a significant number of children with mild-to-moderate HI have age-appropriate language abilities.